The role of CD40 in CD40L- and antibody-mediated platelet activation - Langer, Florian; Ingersoll, Susan B.; Amirkhosravi, Ali; Meyer, Todd; Siddiqui, Farooq A.; Ahmad, Sarfraz; Walker, Jamie M.; Amaya, Mildred; Desai, Hina; Francis, John L. (Thrombosis and Haemostasis, 2005)
Our initial finding that CD40– and CD40 ligand (CD40L)-deficient mice displayed prolonged tail bleeding and platelet function analyzer (PFA-100) closure times prompted us to further investigate the role of the CD40-CD40L dyad in primary hemostasis and platelet function. Recombinant human soluble CD40L (rhs CD40L), chemical cross-linking of which suggested a trimeric structure of the protein in solution, activated platelets in a CD40-dependent manner as evidenced by increased CD62P expression. CD40 monoclonal antibody (mAb) M3, which completely blocked rhs CD40L-induced platelet activation, also prolonged PFA-100 closure times of normal human blood. In contrast, CD40 mAb G28–5 showed less potential in blocking rhs CD40L-induced CD62P expression and did not affect PFA-100 closure times. However, when added to the platelets after rhs CD40L, G28–5 significantly enhanced the platelet response by causing clustering of, and signaling through, FcγRII. Similarly, higher order multimeric immune complexes formed at a 1/3 molar ratio of M90, a CD40L mAb, to rhs CD40L induced strong FcγRII-mediated platelet activation when translocated to the platelet surface in a CD40-dependent manner, including the induction of morphological shape changes, fibrinogen binding, platelet aggregation, dense granule release, microparticle generation and monocyte-platelet-conjugate formation. The results suggest that CD40 may play a role in primary hemostasis and platelet biology by two independent mechanisms: First, by functioning as a primary signaling receptor for CD40L and, second, by serving as a docking molecule for CD40L immune complexes. The latter would also provide a potential mechanistic explanation for the unexpected high incidence of CD40L mAb-associated thrombotic events in recent human and animal studies.Parts of this work have been presented on the 46th Annual Meeting of the American Society of Hematology (San Diego, 2004).
Keywords: Platelet physiology; platelet immunology; platelet activation markers; animal models